Breast Implant–Associated Anaplastic Large Cell Lymphoma in Australia and New Zealand: High-Surface-Area Textured Implants Are Associated with Increased Risk. Issue 4 (October 2017) - Loch-Wilkinson, Anna; Beath, Kenneth J.; Knight, Robert John William; Wessels, William Louis Fick; Magnusson, Mark; Papadopoulos, Tim; Connell, Tony; Lofts, Julian; Locke, Michelle; Hopper, Ingrid; Cooter, Rodney; Vickery, Karen; et al.
Abstract : Background: The association between breast implants and breast implant–associated anaplastic large cell lymphoma (ALCL) has been confirmed. Implant-related risk has been difficult to estimate to date due to incomplete datasets. Methods: All cases in Australia and New Zealand were identified and analyzed. Textured implants reported in this group were subjected to surface area analysis. Sales data from three leading breast implant manufacturers (i.e., Mentor, Allergan, and Silimed) dating back to 1999 were secured to estimate implant-specific risk. Results: Fifty-five cases of breast implant–associated ALCL were diagnosed in Australia and New Zealand between 2007 and 2016. The mean age of patients was 47.1 years and the mean time of implant exposure was 7.46 years. There were four deaths in the series related to mass and/or metastatic presentation. All patients were exposed to textured implants. Surface area analysis confirmed that higher surface area was associated with 64 of the 75 implants used (85.3 percent). Biocell salt loss textured (Allergan, Inamed, and McGhan) implants accounted for 58.7 percent of the implants used in this series. Comparative analysis showed the risk of developing breast implant–associated ALCL to be 14.11 times higher with Biocell textured implants and 10.84 higher with polyurethane (Silimed) textured implants compared with Siltex textured implants. Conclusions: This study has calculated implant-specific risk of breast implant–associated ALCL. Higher-surface-area textured implants have been shown to significantly increase the risk of breast implant–associated ALCL in Australia and New Zealand. The authors present a unifying hypothesis to explain these observations. Abstract : Supplemental Digital Content is available in the text.